Entrepreneurship in Singapore. - Lim, Sing wei. (2008)
In view of the importance of entrepreneurship to Singapore's future growth and prospects, this paper aims to give recommendations on how to promote entrepreneurship in Singapore. It is based on an analysis of the mindset of young Singaporeans towards entrepreneurship and other related issues.